Implementasi Augmented Reality Sebagai Media Pembelajaran Kata Benda Bahasa Arab pada Siswa Sekolah Dasar Islam Terpadu - Dini Destiani Siti Fatimah; Ayu Latifah; Hani Haniyah (Jurnal Algoritma, 2022)
The rapid development of technology to this day has brought positive developments and progress to the world of education with the creation of various learning media. Learning media are diverse and can be used in various kinds of science, one of which is linguistics. Language science in the world of education is one of the important subjects, one of which is Indonesian. In addition, there are several other languages ​​that must be learned, one of which is Arabic. Indonesia is one of the countries with the largest number of Muslims in the world, and Arabic is one of the important curriculum subjects in the field of Islamic education, such as Islamic boarding schools or Islamic boarding schools. Islam. Augmented Reality technology is a technology that takes two aspects, namely the real world and the virtual world, one of the technologies used in AR is a camera accompanied by the use of the Multimedia Development Life Cycle method which consists of six stages, namely Concept, Design, Material Collecting, Assembly, Testing. , Distributions. Also, by using several tools and materials in the form of Hardware ASUS A456U and Samsung J6 + with the software used by Unity. In this case, the use of learning media with digital AR technology is made for Integrated Islamic Elementary School students, in which there are Arabic language subjects as a language that must be learned and known in the teaching and learning process.